Los pieds-noirs en el desarrollo turístico alicantino - Mariana Dominguez Villaverde (Cahiers de Civilisation Espagnole Contemporaine)
This article analyses the contribution of the pieds-noirs to the development of tourism in Alicante from a transnational historical perspective. The settlement of several tens of thousands of Europeans from Algeria in the province of Alicante from the end of the 1950s, as a consequence of the war and the independence of the French colony, had a great impact on the local economy, particularly in the field of tourism, which began to take off in the 1960s.